Family-Resourced Early Intervention Program for Motor Development in Cerebral Palsy Children - Sumaryadi, Muhammad Mufti Rakadia (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
This research was conducted to determine the results of implementing an early intervention program Family resource for children's motor development applied to cerebral children palsy aged 4 years. The research method used in this research is research. The experiment takes the form of Single Subject Research (SSR) with data collection techniques including GMFM and GMFCS tests, interviews, and observations. The results of this research, this program has successfully demonstrated significant progress in control development better head in children. This increase can be seen from the longer duration in Doing various activities shows that the child has started to have neck strength enough to support the head, especially when sitting with assistance. Results from research It is hoped that this can become a reference for educators, especially in improving motor development of children with cerebral palsy at an early age.